EduMangrove SMAN 6 Tanjungpinang: Integrasi Multimedia Pembelajaran pada Proyek Kolaboratif Berkelanjutan untuk Pelestarian Pantai Sebauk Laut, Kota Tanjungpinang dari Abrasi - Fitriani, Rita; Fernando, Adam; Anggraini, Rika; Hasdari, Putri; Oktaviani, Elisa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The EduMangrove community service activity at SMAN 6 Tanjungpinang aims to raise awareness and increase students' concern for the Sebauk Laut coastal environment through education by integrating creative and innovative learning multimedia in the form of documentary videos and video demonstrations about the importance of mangroves for preserving the Sebauk Laut beach from abrasion, as well as involving students in real action in a sustainable collaborative project to plant mangroves. This activity succeeded in increasing students' awareness and concern for the Sebauk Laut coastal environment. Apart from that, this activity also provides a significant increase in students' knowledge regarding the importance of the mangrove ecosystem as protecting the Sebauk Laut coastline from abrasion, as well as practical skills in planting mangroves properly and correctly in areas that are prone to abrasion. Evaluation was carried out through the distribution of pre- and post-education questionnaires, observations and interviews, which showed a significant increase in students' environmental awareness, knowledge and skills. The EduMangrove program shows the great potential of using multimedia learning in increasing environmental awareness and student involvement in coastal conservation efforts.